Hubungan Pengetahuan Dengan Kepatuhan Pejabat Fungsional Perawat Puskesmas Dalam Usulan Penilaian Angka Kredit Di Wilayah Kerja Dinas Kesehatan Kota Palangka Raya - Meilitha Carolina; Ayu Puspita; Antonia Mariana Dayman (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Credit Score is a unit of value from the description of activities and/or the accumulated value of the description of activities that must be achieved by nurses in the context of developing the career concerned. Correct knowledge of scoring credit scores is the main basis for the compliance of a functional nurse official in submitting or preparing proposals for assessing credit scores. The lack of knowledge that nurses have about the proposed assessment of credit scores is at risk for these nurses who are considered disobedient resulting in delays in promotion and promotion. This research is to find out the relationship between knowledge and the compliance of functional officers of puskesmas nurses in the proposed credit score assessment in the Work Area of the Palangka Raya City Health Office in 2022. The research method used in this research is a correlational research using a cross-sectional research design. Data collection was carried out using a knowledge questionnaire totaling 15 questions and observing compliance using a checklist sheet containing 10 questions. Research shows that the level of knowledgenurse functional officials regarding Credit Scores, namely 9 respondents (14%) have good knowledge, 54 respondents (84%) have sufficient knowledge and 1 respondent (2%) have less knowledge. As for the research results for compliance from respondents, it was found that 62 respondents (97%) obeyed and 2 respondents (3%) did not comply. The results of statistical analysis using the Rank Spearman correlation test showed that the strength of the relationship between variables was expressed in a positive correlation coefficient of 1 with a very significant level of closeness (p value = 0.028). Based on this research, it is recommendedfor functional nurse officials to be more disciplined and punctual in carrying out the proposals for assessing credit scores that have been set 2 (two) times in the period at the end of June and the end of December.